MONITORING AND REPORTING DELAYED ADVERSE REACTION TO NONIONIC CONTRAST MEDIA - Sungworn, Supattra; Muangsomboon, Kobkun; Suwatananonthakij, Tarntip; Phattanarudee, Siripan (Thai Bulletin of Pharmaceutical Sciences, 2021)
Delayed adverse reaction from nonionic contrast media (nonionic-CM) is not often monitored by healthcare professional and it can be explained from the fact that most of patients develop symptoms after they have been discharged from the hospital. Therefore, the patients may be affected from this condition. The objective of this study was to investigate the reports of delayed adverse reaction from nonionic-CM, clinical manifestation, onset of reaction and primary self-management of patients. This prospective descriptive study was proceeded in patients who underwent the enhanced computerized tomography scan (CT scan) at Siriraj imaging center (outpatients) between November 2019 - March 2020. There were 434 patients recruited into this study and they were divided into 2 groups: Group 1 (87 patients), patients who had acute allergic reaction (within 1 hour after CT scan) and group 2 (347 patients), patients who did not have acute allergic reaction. Both groups were followed-up by telephone at 24 hours and 7 days after receiving nonionic-CM. A total of 61 patients (14.1%) was reported for the delayed adverse reaction and most of them was physiological reaction (82%), while allergic-like reaction was found in 19.7%. Delayed adverse reaction can still be occurred in patient who used to have acute allergic-like reaction. Therefore, healthcare professional should advise all patients about delayed adverse reaction whether they had acute allergic-like reaction. If the patients have the delayed adverse reaction (allergic-like reaction), they should have come back to the hospital for diagnosis and treatment. In addition, they should be given the drug-allergy card and their allergy should be recorded in the system. This can be helpful for monitoring and preventing the repeated allergic reaction to the same nonionic-CM.